THE PARADOX OF DIGITAL ARCHIVAL TRANSFORMATION IN LOCAL GOVERNMENT: A CASE STUDY OF SOUTH BOLAANG MONGONDOW, INDONESIA - Dian Ekawati Moha; Sudarsono; Djamila Podungge (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The management of government archives is a mandatory administrative affair that serves as the backbone of state accountability and institutional memory. However, peripheral regions in Indonesia often face a